Case Study: Use of Dry Mix Concrete as a Substitute Material for Ready Mix Concrete on Development Projects OCC Building – Jabodebek Lrt Depot - Raden Herry Shufi; Pio Ranap Tua Naibaho (Syntax Corporation Indonesia, 2023)
The construction of the OCC Building is the main target for all buildings that must be completed in the Depo LRT Jabodebek area, which is located in Jatimulya, East Bekasi. In writing this thesis, only explain the stages of the work of casting concrete for the building structure on upper of foundation. The condition of a very large area with various other construction works around it and very limited implementation time requires contractors to be creative and find solutions on the most effective and efficient methods. The construction of this OCC Building uses concrete construction with the quality of K-250 (fc'20.75 MPa) and K-350 (fc'29.05 MPa). The problem that occurs is because this located area between the side of the Jakarta-Cikampek Toll Road and the edge of Kalimalang, which also contains the Kalimalang highway, both of which are roads that have very heavy traffic flows, so an alternative method of concrete casting work is needed. This project uses 2 casting methods, is to use Ready Mix concrete and Dry Mix concrete. While the writing of this case study only reviews the aspects of quality, time, and cost if the construction method for casting uses only Dry Mix concrete as a replacement material for Ready Mix concrete. It can be concluded that if only viewed from the cost of casting, using Dry Mix concrete requires higher costs than Ready Mix, but if viewed as a whole from all aspects of work costs, using Dry Mix can increase time efficiency in project completion, so that it can affect cost efficiency which at the end of the project can be completed faster at lower costs. While from the results of data processing with the method of Analytical Hierarchy Process (AHP), Dry Mix concrete is preferred by respondents, it can be concluded that Dry Mix concrete is better than Ready Mix concrete for the construction project of OCC Building-Depo LRT Jabodebek